1993
DOI: 10.1002/ar.1092350217
|View full text |Cite
|
Sign up to set email alerts
|

Star volume in bone research. A histomorphometric analysis of trabecular bone structure using vertical sections

Abstract: Conventional bone histomorphometry performed on iliac crest biopsies does not generally provide unbiased stereological estimates of parameters related to bone structure due to the anisotropy of trabecular bone; this, however, can be obtained with vertical sections, which are anisotropic sections, in combination with an anisotropic test system. A practical procedure for obtaining vertical sections from bone is described. The new stereological parameter, the star volume, can provide an unbiased estimation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 43 publications
0
10
0
1
Order By: Relevance
“…(9) These calculations demand the presence of a steady state between resorption and formation. (9) Marrow star volume, which reflects the degree of trabecular disintegration caused by perforating resorption, was measured according to the method of Vesterby et al (10) In 17 women from the HRT group and 18 from the pla-cebo group, we succeeded in getting evaluable pre-and post-treatment biopsies. The subsequent analysis is based on these biopsies only.…”
Section: Methodsmentioning
confidence: 99%
“…(9) These calculations demand the presence of a steady state between resorption and formation. (9) Marrow star volume, which reflects the degree of trabecular disintegration caused by perforating resorption, was measured according to the method of Vesterby et al (10) In 17 women from the HRT group and 18 from the pla-cebo group, we succeeded in getting evaluable pre-and post-treatment biopsies. The subsequent analysis is based on these biopsies only.…”
Section: Methodsmentioning
confidence: 99%
“…1 Anterior section, 2 middle section, and 3 posterior section. Directional body axes based on the comparative anatomy approach proposed by Stasek (1963) Aquacult Int (2009) 17:491-506 495 The gonadal biomass (GB) was determined by extrapolation stereology principle described by Versterby (1993): GB = (W vm 9 GA)/100, where GB is the gonadal biomass in g (wet weight), GA is the mean percentage of gonadal area (in % of the mean of the three sections for each individual), and W vm is the visceral mass (gonad ? digestive gland) in g (wet weight).…”
Section: Quantitative Analysesmentioning
confidence: 99%
“…16,19 The most common method for quantifying the fabric of TB networks is the mean-intercept-length method ͑MIL͒ introduced by Whitehouse in 1974. 20 Other volumetric approaches, such as volume orientation 21 and star volume distribution, 22 have also been used to characterize trabecular morphology. Harrigan and Mann 23 showed that the MIL method applied in three dimensions produces a second-rank tensor that characterizes the structural anisotropy of materials with at least orthotropic symmetry.…”
Section: Introductionmentioning
confidence: 99%